2011
DOI: 10.1007/s13238-011-1104-4
|View full text |Cite
|
Sign up to set email alerts
|

Role of plant autophagy in stress response

Abstract: Autophagy is a conserved pathway for the bulk degradation of cytoplasmic components in all eukaryotes. This process plays a critical role in the adaptation of plants to drastic changing environmental stresses such as starvation, oxidative stress, drought, salt, and pathogen invasion. This paper summarizes the current knowledge about the mechanism and roles of plant autophagy in various plant stress responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
98
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(100 citation statements)
references
References 51 publications
2
98
0
Order By: Relevance
“…Yet, the contribution of autophagy to seedling establishment under stressful environments and the association between autophagy and leaf senescence are not completely understood (Hanaoka et al, 2002;Han et al, 2011). We have previously shown that suppression of both ATI1 and ATI2 delays seed germination on media containing the germination suppression and abiotic stress-related hormone abscisic acid .…”
Section: Ati1 Is a Stress-and Senescence-associated Multifunctional Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, the contribution of autophagy to seedling establishment under stressful environments and the association between autophagy and leaf senescence are not completely understood (Hanaoka et al, 2002;Han et al, 2011). We have previously shown that suppression of both ATI1 and ATI2 delays seed germination on media containing the germination suppression and abiotic stress-related hormone abscisic acid .…”
Section: Ati1 Is a Stress-and Senescence-associated Multifunctional Pmentioning
confidence: 99%
“…One of the central cellular machineries allowing plants to survive energy-depleting stresses is macroautophagy, hereafter referred to as autophagy. Starvationinduced autophagy is classically associated with bulk turnover of macromolecules and organelles in the vacuole upon exposure to stresses causing extensive energy deprivation (Han et al, 2011;Hayward and Dinesh-Kumar, 2011;Li and Vierstra, 2012;Yoshimoto, 2012). In addition, autophagy targets specific proteins, protein aggregates, or organelles for recycling in the vacuole by a process called selective autophagy (Floyd et al, 2012;Li and Vierstra, 2012;Schreiber and Peter, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In plants, autophagy can be induced by both abiotic and biotic stresses, such as starvation, oxidative stress, drought, salt, and pathogen invasion (Bassham, 2007;Han et al, 2011;Hayward and Dinesh-Kumar, 2011;. Generally, autophagy can be divided into three main types, including macroautophagy, chaperone-mediated autophagy, and microautophagy (Xie and Klionsky, 2007;Reggiori and Klionsky, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…These gene products can be divided into several functional groups: the ATG1-ATG13 kinase complex, ATG9 and ATG9-associated proteins, a phosphatidylinositol 3-kinase complex, and two ubiquitin-like conjugation systems (Xie and Klionsky, 2007). Recent studies show that plant autophagy participates in multiple physiological processes, such as nutrient recycling, development, senescence, abiotic stress responses, and pathogen defense (Doelling et al, 2002;Hanaoka et al, 2002;Liu et al, 2005Liu et al, , 2009Bassham, 2007;Han et al, 2011). ATG3 is an E2-like conjugating enzyme that can catalyze the ATG8-PE conjugation formation during autophagy process (Ichimura et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…It is also a key factor for recruiting cargo to the growing autophagosome during selective autophagy (Noda et al 2010;Han et al 2011). Yeast has only a single ATG8 protein while humans have seven ATG8 proteins divided into two subfamilies [LC3 and GABARAP/GATE-16, as reviewed by (Behrends and Fulda 2012)] and Arabidopsis has nine .…”
Section: Selective Autophagymentioning
confidence: 99%